Pengembangan smart environment di Kampung Wisata Jetisharjo RW. 07, Yogyakarta - Van Basten Maria Fernandes Koy; Olinda Rodrigues (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2019)
Developing smart environment at Tourism spots in Jetisharjo RW. 07, Yogyakarta The development of tourism sector in the city of Yogyakarta nowadays is more inclined to urban tourism as the impact of the globalization of tourism. Tourism activities may bring physical and non-physical changes towards characteristics of a place that has been developed to become a tourism site like Kampung Jetisharjo RW. 07. Therefore, research needs to be done with a smart city approach, particularly the smart environment as a preliminary study to formulate a planning strategy is a smart and sustainable environment. In this study, qualitative method was used. The data are primary data and secondary data. The secondary data include the dimension of the smart city which is a smart environment. The primary data on the other hand obtained through field observation, photo taking and interviews with local people. This study shows that tourism development in Jetisharjo RW 07 not only for the existence of modern technology, but also on the capacity and participation of local communities as the actors in the development of tourism. © 2019 Van Basten Maria Fernandes Koy, Olinda Rodrigues